1998
DOI: 10.1162/jiec.1998.2.2.89
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of Electric Motors in Consumer Products

Abstract: Summary Product takeback calls for sound strategies of product recovery management One such strategy‐is the reuse of the components of a product. There are consumer products such as power tools whose most expensive component, the electric motor; offers potential for reuse. Empirical evidence reveals that the lifetime of a motor often exceeds the life‐time of the product using it. This article focuses on the reuse of electric motors. For this purpose, a novel circuit was developed that measures, computes, and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
2

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(35 citation statements)
references
References 4 publications
0
31
0
2
Order By: Relevance
“…Klausner et al [30] analyzed the trade-off between the higher initial manufacturing costs caused by using an electronic data log (EDL) in products and the cost savings from the reuse of used motors. Simon et al [31] improved the cost-benefit analysis of Klausner et al [32] by taking into consideration the limited lifespan of a product's design.…”
Section: Sensor Embedded Productsmentioning
confidence: 99%
“…Klausner et al [30] analyzed the trade-off between the higher initial manufacturing costs caused by using an electronic data log (EDL) in products and the cost savings from the reuse of used motors. Simon et al [31] improved the cost-benefit analysis of Klausner et al [32] by taking into consideration the limited lifespan of a product's design.…”
Section: Sensor Embedded Productsmentioning
confidence: 99%
“…Although the majority of the studies presented above focus on the development of SEP models that enable product data acquisition during their life cycle and/or in their EOL phase, only a select few number of researchers have conferred a cost-benefit analysis. Klausner, Grimm and Hendrickson (1998a) analyzed the trade-off between the higher initial manufacturing costs caused by using an electronic data log (EDL) in products and the cost savings from the reuse of used motors. Simon et al (2001) improved the cost-benefit analysis of Klausner, Grimm and Hendrickson (1998b) by taking into consideration the limited lifespan of a product's design.…”
Section: Sensor Embedded Productsmentioning
confidence: 99%
“…Although most of these studies focus on the development of SEP models, only few researchers presented a cost-benefit analysis. [29] analyzed the trade-off between the higher initial manufacturing cost caused by the use of an electronic data log in products and cost savings from the reuse of used motors. [30] improved the cost-benefit analysis of [29] by considering the limited life of a product design.…”
Section: Literature Reviewmentioning
confidence: 99%
“…[29] analyzed the trade-off between the higher initial manufacturing cost caused by the use of an electronic data log in products and cost savings from the reuse of used motors. [30] improved the cost-benefit analysis of [29] by considering the limited life of a product design. They showed that, in that case, servicing provides more reusable components compared to EOL recovery of parts.…”
Section: Literature Reviewmentioning
confidence: 99%